Bound spin-excitons in two-dimensional electron gas - Fleurov, V.; Kikoin, K. (Физика низких температур, 2001)
A theory

of the spin exciton capture by a magnetic impurity in a 2D electron gas is developed. We

consider a resonance model for the electron scattering by a transition metal impurity and

calculate the binding potential for spin excitons. This potential is spin selective and is

capable of binding a spin exciton with zero angular momentum. In order to trap an exciton

with a nonzero angular momentum m, the potential must exceed a certain threshold value,

depending on m.